Anne Sofie von Otter and Marc Minkowski perform Canteloube and Mozart Verbier Festival 2010 - Canteloube, Joseph 1879-1957; Mozart, Wolfgang Amadeus 1756-1791 (Idéale Audience, 2010)
Canteloube, Chants d'Auvergne Canteloube was born in Auvergne, the French region immortalized in his arrangements of folk-songs. He had been a pupil at the Schola Cantorum at the beginning of the 20th century and had studied with Vincent d'Indy and Albert Roussel. This might suggest severity and objectivity in his works but this is not apparent in his succulent Songs of the Auvergne. All his passion for his native region is poured into these arrangements, whose evocative orchestration and gorgeous harmony envelop the simple tunes like an act of love. Mozart, Symphony No. 39 No one knows why Mozart composed his last three symphonies in 1788. Perhaps he intended to add more and publish a set of six or maybe he put them in a drawer in the hope they might one day lead to employment. Whatever the case, all three are full of innovations. Unusually for Mozart, this symphony opens with a grand introduction although the overwhelming characteristics of the symphony are lyricism and a subtle interplay between the orchestral forces. © Verbier Festival 2010
Keywords: Songs (Medium voice) with orchestra; Songs, Occitan; Symphonies; Internet videos